Contribution of self-compassion to rumination in the 2022 Padang State University Fresh Graduate Jobseeker Competition - A. Dharmawan,; E. Magistarina, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The reluctance to apply for jobs over an extended period and the intense competition faced by recent graduates can lead to self-blame and a ruminative thinking style characterized by persistent negative thoughts and difficulty finding solutions to problems. Embracing both positive and negative experiences as learning opportunities is crucial. This study, conducted at Padang State University in 2022, aimed to quantify self-compassion's impact on job-seeking fresh graduates' rumination. A quantitative research approach, purposive sampling, was employed to select 289 participants based on specific criteria. The instruments for measuring self-compassion and rumination were adapted from Sugianto et al. and Yusainy, respectively. The findings indicate that self-compassion has a significant negative correlation with rumination, accounting for 27.7% of its variance.